McGurk effect in Polish listeners - Wojciech MAJEWSKI (Archives of Acoustics)
The phenomenon of a multi-modal interaction between audio and video stimuli, called the McGurk effect, was investigated for the Polish subjects. Two experiments were performed. In the first experiment the occurrence of McGurk effect for Polish speech was examined. The results of the first experiment for which over 94% of listeners' answers were consistent with the audio stimuli indicated that generally it is very difficult to evoke the McGurk effect in Polish listeners. In the second experiment the stimuli for which the McGurk effect was distinctly present were subjected to different kind of audio or video distortions and presented to the listeners. The distortions in the visual signals resulted in an increase of the answers consistent with the audio stimuli while the distortions in the audio signals resulted in an increase of the answers consistent with the visual stimuli.